Convective heat transfer characteristics of supercritical carbon dioxide in vertical miniature tubes of a uniform heating experimental system. (March 2021) - Wang, Lei; Pan, Yu Cheng; Lee, Jin Der; Fu, Ben-Ran; Pan, Chin
Highlights: The local heat transfer characteristics of supercritical CO2 are investigated. The parametric effects on the local heat transfer performance are discussed. The optimal heat flux with the best thermal performance is identified. The thermal performance of horizontal flow is better than upward flow. The new correlation can suitably predict the local heat transfer characteristics. Abstract: This study experimentally investigates the local convective heat transfer characteristics of supercritical carbon dioxide in vertical and uniformly-heated miniature tubes with inner diameters of 0.5, 0.75, and 1.0 mm, and compares with that for horizontal flow. The effects of outlet pressure, heat flux, mass flux, inlet temperature, and tube diameter on the local heat transfer are explored through the evaluation of local heat transfer coefficient and local wall temperature. The results reveal that the non-heat-transfer-deterioration (non-HTD) mode is prevalent for upward flow in the vertical miniature tubes because of the effects of buoyancy and flow acceleration. The optimal heat flux for the best heat transfer performance occurs when the outlet fluid temperature is close to the corresponding pseudocritical point. Moreover, the local heat transfer coefficient increases with an increase in the mass flux but decreases with an increase in the inlet fluid temperature or tube diameter. An increase in the outlet pressure causes increases in the fluid and wall temperatures. The experimental results show that the buoyancy effect would promote the local heat transfer for vertical downward flow but deteriorate that for vertical upward flow, particularly after the pseudo-critical region. The horizontal flow would present the best heat transfer performance when the outlet flow condition is near the pseudo-critical point, while the vertical downward flow is superior for the system with the outlet fluid temperature substantially higher than the pseudo-critical point. The new empirical correlation developed can predict very well the present data set of local Nusselt number for upward flow in vertical uniformly-heated tubes within a relative error of ±20%.